MORFOLOGI SEMAI BEBERAPA JENIS PALEM HIAS Seedling morphology of some ornamental palms - Ning Wikan Utami; Hartutiningsih M Siregar (Research Center for Biology-Indonesian Institute of Sciences, 1998)
The results of 18 palms species studied showed that there were three species (Livistona chinensis (Jack) R.Br.ex Mart,Thrinax sp.and Sabal meeacarpg Small) which their cotyledone growth under ground level (group I), their first leaf did not cleave, these had two types of germination i.e. remote tubular (L. chinensis and Thrinax sp.)and remote ligular (S. meeacarpa).Thirthteen species (Heterosphate elata Scheff, Archonthophoenic alexandrae Wendl.& Drude, Areca triandra Roxb., Bentinckia nicobarica (Kurz.) Becc, Chrvsalidocarpus sp., C. lutescens H. Wendl.,Cvrtostachvs eleeans Burret, C.renda Blume, Drvmoploeus pachvcladus H.E.Moore, Neodypsis decarvi Jumelle,Oenocarpus panamanus L.H.Bailey, Pthvchosperma eleeans (R.Br.) Blume and Pritchardia pacifica Seem. & H.Wendl.) produce their cotyledone near ground level (group H), their first leaf cleft into two parts except on the species O. panamanus cleft into four parts, all of these species had adjacent ligular type of germination. There was large variability on the germination.The range of first germination was 12105 days after sowing, last germination was in the range of 78-212 days and the germinationpersentage was 1.3-94.0%.